(untitled) (Vietnam Journal of Community Medicine, 2021)
Objective: Evaluate the difficulty of extraction of lower wisdom teeth according to Parant at Thai Binh Medical University Hospital. Subjects and methods: Descriptive study through cross-sectional investigation of 143 subjects with lower wisdom teeth surgery at Thai Binh Medical University Hospital from November 2019 to June 2020. Results: The percentage of missing wisdom teeth was about 57.34%; stuck (position A2) for 47.55%; Far/horizontal deviation accounted for 37.06%, proximal deviation accounted for 33.57%, there was no case of inverted lower wisdom teeth; The morphology of lower wisdom teeth has 1 foot or many legs bunched for 41.96%; density of lower jaw bone is mainly type II (normal) for 86.01%; ligament light around the teeth at normal level accounted for the most with 93.71%. Conclusions: The level of difficulty in extraction of lower wisdom teeth has an average score of 11.83 ± 2.09.